2021
DOI: 10.1001/jamanetworkopen.2021.8386
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Microbiota and Infectious Complications After Elective Surgical Procedures

Abstract: This case-control study investigates the association between nasal microbial profiles and odds of infection after elective surgical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…A recent anesthesiology-led study of preoperative nasal microbiome characterization builds upon this concept, demonstrating that, even after adjustment for S. aureus carriage, preoperative microbiome “cluster” is a stronger predictor of postoperative infection than traditional clinical factors such as age, procedure type, and medical comordibity. 16…”
Section: Paradigm 2: Antimicrobial Resistance and Surgical Antibiotic...mentioning
confidence: 99%
See 2 more Smart Citations
“…A recent anesthesiology-led study of preoperative nasal microbiome characterization builds upon this concept, demonstrating that, even after adjustment for S. aureus carriage, preoperative microbiome “cluster” is a stronger predictor of postoperative infection than traditional clinical factors such as age, procedure type, and medical comordibity. 16…”
Section: Paradigm 2: Antimicrobial Resistance and Surgical Antibiotic...mentioning
confidence: 99%
“…A recent anesthesiology-led study of preoperative nasal microbiome characterization builds upon this concept, demonstrating that, even after adjustment for S. aureus carriage, preoperative microbiome "cluster" is a stronger predictor of postoperative infection than traditional clinical factors such as age, procedure type, and medical comordibity. 16 Challenges to realizing the potential of preoperative screening include the growth of remote preoperative evaluation and actionable test turnaround times in cases of urgent or emergent surgery. Experience and innovation in high-reliability preoperative microbiologic screening developed during the COVID-19 pandemic may enable health systems to address these challenges more effectively: molecular diagnostic platforms acquired by many hospital laboratories for rapid preoperative SARS-CoV-2 screening can be repurposed for quick, highly accurate detection of methicillin-resistant S. aureus using alternative cartridges 49 (e.g., to determine optimal prophylaxis for trauma patients requiring orthopedic implants shortly after admission).…”
Section: Updates In Prevention Of Surgical Site Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…NKTCL, featured by angioinvasion, angiodestruction, necrosis and strong linkage to Epstein-Barr virus (EBV), is a rare but highly aggressive disease commonly involving the nasal cavity and UAT (Li et al, 2013;Tse et al, 2019). Recently, nasal microbiome has been reported to be a useful tool and biomarker in the clinical management of multiple diseases (Mahdavinia et al, 2018;Perez-Losada et al, 2018;Rhee et al, 2018;Hsiao et al, 2021). Nevertheless, the role of the nasal microbes in the complex interplay between the host and environment is far from understood.…”
Section: Discussionmentioning
confidence: 99%
“…The most common genera defined in healthy individuals in the Human Microbiome Project are Staphylococcus, Corynebacterium, Propionibacterium , and Moraxella (1). Subsequent studies on the nasal microbiota have revealed microbiota dysbiosis in diseased states such as chronic rhinosinusitis (2) and have linked the nasal microbiota to infectious complications after elective surgical procedures (3).…”
Section: Introductionmentioning
confidence: 99%